Influence of cooling conditions and amount of retained austenite on the fracture of austempered ductile iron - VYACHESLAV GORYANY; ECKART HOFMANN; PAUL JOSEF MAUK (Journal of the Serbian Chemical Society, 2008)
SEM Analysis of fracture surfaces from tensile test specimens of thick-walled, austempered ductile irons (diameter 160 mm) shows different fracture behavior depending on the austenite retained in the matrix. The results show ductile fractures only in areas containing retained austenite sections. In section areas without or with a very low content of retained austenite, only brittle fracture without any plastic deformation occurs. The content of retained austenite determines the amount of ductile fracture in the microstructure.